ANALISIS DISKRIMINATIF TERHADAP PEREMPUAN DALAM NOVEL KEMBALI KE BATAVIA KARYA GIGREY - Echa Rosyidah; Yuniseffendri (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the forms of discrimination, the forms of inequality according to Mansour Fakih, and the relationship between the two. This study employs a qualitative descriptive method, utilising data collection techniques such as documentation and literature review. The results indicate the existence of six forms of discrimination against female figures and five forms of gender inequality according to Mansour Fakih. The most prevalent form of discrimination is violence against women, whilst the least common is the exploitation of women. The most frequently identified form of inequality according to Mansour Fakih is violence, whilst the least common is excessive workload. The findings reveal a correlation between forms of discrimination and gender inequality such as marginalisation, subordination, stereotyping, violence, and excessive workload.